MAQASID AL-SYARI’AH (AL-DHARURIYAT, AL-TAHSINIYAT, AL-HAJIYAT) - Mahmud, Muhammad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2020)
Maqashid al-syari'ah is al-ma'ani allati syuri'at laha al-ahkam (value content which is the purpose of law enforcement). Observing the three levels mentioned above, it can be said that for the level of daruriyyat, then in ushul fiqh it is categorized as amulet. At the hajiyyat level, it is categorized as rukhshah. Where as at the tahsiniyyat level, it is in the form of a complement which may contain elements of local customs (‘urf). The level of application of maqashid al-syari'ah in a legal provision is still based on the priority level which is considered standard. Unless it collides at the daruriyyat level, between maintaining religion at the first level and caring for the soul at the second level, then the form of solution can prioritize the safety of the soul. After the needs of dharuriyat and hajiyat are met, (by still prioritizing dharuriyat needs over hajiyat), then it is permissible to meet the needs of tahsiniyat, however, with the requirements, namely, if the primary and second needs are met without reducing the purpose of Allah and the servant.